Oral mucositis in children suffering from acute lymphoblastic leukaemia - Pels, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Oral mucositis is the most commonly reported side effect observed in neoplastic patients treated with chemotherapy and radiotherapy of the head and neck region as well as in patients who have received a haematopoietic stem cell transplant. The aim of the study was to assess the oral mucosa status in children with acute lymphoblastic leukaemia (ALL) during antineoplastic therapy. Material and methods : The clinical examination included 78 children aged 2-18 with ALL. The clinical examination was conducted using the dental preset tray. The condition of the oral mucosa was determined using the WHO scale for oral mucositis . Results : In the first period of antineoplastic therapy the pathological lesions of the oral mucosa of the mucositis type were observed among the examined patients. The lesions had various levels of intensity. Pain was found to be the primary symptom of oral mucositis . In this study the following were observed: local erythema of the oral mucosa in 35%, white pseudomembranous lesions in 18%, erosions in 40% and oral ulcerative lesions in 4% of patients who underwent the antineoplastic therapy. Oral mucositis was observed in 3.17% of children after 6 months of chemotherapy. Conclusion : Local treatment of oral mucositis with polyantibiotic-antifungal mixture, supporting antifungal systemic treatment, and improving the overall peripheral blood conditions in children suffering from acute lymphoblastic leukaemia improve the condition of the oral mucosa.